2019
DOI: 10.1617/s11527-019-1372-7
|View full text |Cite
|
Sign up to set email alerts
|

Picture frame and diagonal compression testing of cross-laminated timber

Abstract: Currently, no appropriate standard exists that describes how to determine the in-plane shear stiffness for cross-laminated timber (CLT) panels, meaning that, there is a lack of appropriate and reliable test methods. In this paper, two gross shear test methods are evaluated: a picture frame test and a diagonal compression test, which are intended to measure the shear stiffness of a whole CLT panel. This evaluation aimed to compare the shear modulus, the amount of compression/tension in the diagonal directions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 7 publications
2
22
0
2
Order By: Relevance
“…In the diagonal compression test method, a square CLT panel was compressed in one diagonal direction by a displacement controlled hydraulic jack. Please refer to [5,6] for more details on the test procedure. During a diagonal compression test, only one diagonal was compressed, and the second diagonal was left without control of the displacement.…”
Section: Diagonal Compression Testmentioning
confidence: 99%
See 4 more Smart Citations
“…In the diagonal compression test method, a square CLT panel was compressed in one diagonal direction by a displacement controlled hydraulic jack. Please refer to [5,6] for more details on the test procedure. During a diagonal compression test, only one diagonal was compressed, and the second diagonal was left without control of the displacement.…”
Section: Diagonal Compression Testmentioning
confidence: 99%
“…Other studies have concluded that board dimensions affect G but not analysed how much. Some studies have calculated G from different variants of the picture frame testing method; see [6][7][8][9], and others have used the diagonal compression test method [5,6,10,11]. Recently, a method similar to the diagonal compression test has been used, but in a more sophisticated way [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations